Equity Conjectures: A Methodological Tool for Centering Social Change in Learning and Design. Issue 1 (2nd January 2022) - Lee, Ung-Sang A.; DeLiema, David; Gomez, Kimberley
Abstract: This article offers methodological insights and tools to those engaged in design-based research (DBR) seeking to advance equity-oriented learning and outcomes through co-design. We respond to recent scholarship that points to the inseparability between the assumptions we hold about society and those we hold about learning, and consider how such insights can inform the methods we employ to facilitate learning in DBR. To do so, we examine the affordances of equity conjectures, statements about how learning remedies socially and historically constructed injustices, within conjecture mapping, a process frequently used in DBR efforts to make assumptions about learning visible to ground design, implementation, and iterative refinement. We share how we made participants' equity conjectures visible in a research-practice partnership (RPP) between university researchers, elementary computer science (CS) curriculum designers, and elementary school teachers. We examine how making these equity conjectures visible during co-design of equity-focused CS lessons facilitated shifts in both the design process and the CS education practices of participating teachers. Our findings point to the utility of explicitly surfacing equity conjectures in collaborative design efforts aimed at equity and justice.